The Effect of Arginine on Some Physiological and Kinematic Variables of the Movement and Starting Stage and the Level of Achievement of the Effectiveness of the 200-meter - Saadoun, Hussein Mohsen (International Journal of Psychosocial Rehabilitation, 2020)
Nutrition is one of the most important factors affecting the training process, so increased attention to athlete's food has increased to compensate for the energy sources that were exhausted during training or competition, so the need to use nutritional supplements as a method to increase the amount of energy in addition to other exercises has increased. The research aims to prepare a curriculum for eating the arginine supplement. Also to know the effect of arginine on the development of some physiological variables and the level of achievement of the research sample, and the research community will be in the deliberate manner that was the hostility of the Maysan governorate team to the effectiveness of the 200-meter enemy for the youth category for the sports year 2019 and the number (10) (2) Runners The number of the research sample was (8) runners and the sample was divided into two equal experimental groups (4) runners and control (4) runners in a random manner. Two players were excluded due to conducting the exploratory experiment on them (80%) from the original community and the most important findings of the research are that The nutritional supplement used by the researchers has led to the development of the physiological variables of the experimental group, and also that arginine has a clear impact in improving the achievement of the effectiveness of the 200-meter enemy. As for the recommendations, it is necessary to clarify the importance of using amino acids for trainers and workers in the field of training and the use of other types of nutritional supplements, except Yen enemy 200 m, in particular, games and field in general.